158k views
3 votes
Find the answer to
SHOW YOUR WORK!
(pls help with dis)
-2x – 6 = -6x – 2​

User Teeknow
by
4.8k points

2 Answers

3 votes

Answer:

x = 1

Explanation:

For this type of equation, you want to combine all like terms. So you can combine the x and the constants. So

-2x - 6 = -6x - 2

+6x +6x

---------------------------

4x - 6 = -2

+6 +6

-----------------

4x = 4

4 multiplied by what number is 4? well 1 so x = 1

User Felixfbecker
by
5.1k points
2 votes
The answer is x=1. I showed my work in the screenshot provided
Find the answer to SHOW YOUR WORK! (pls help with dis) -2x – 6 = -6x – 2​-example-1
User Piohen
by
5.1k points